Near-field MIMO for wireless communication in complex propagation environments - Lodro, Mir (2021)
Communication between chips on integrated packages takes place using conducting wires, vias, microwave transmission lines, inductive and capacitive coupling. Inductive and capacitive coupling for data transfer is impractical for high data rate chip-to-chip communication because of limited scalability and poor performance caused by chip misalignments. Therefore, the solution to overcome this bottleneck is the usage of wireless transmission of information for chip-to-chip or inter-chip communication. Chips are packaged within metal encasing or metal enclosures with electronic circuitry acting as a source of scatterers with a natural tendency to form LOS and NLOS scenarios. Wireless communication between chips under this scenario forms a reverberant cavity where attenuated and phase-shifted multipath fading signals can arrive from directions at different time delays. Such an environment has a high potential to exhibit rich multipath fading characteristics. Therefore, extensive channel measurements are necessary for the statistical characterization of the wireless chip-to-chip channel. An SDR based 2x2 MIMO communication link is created to perform measurements in the mode-stirred metal enclosure by keeping in mind the fact that wireless chip-to-chip communication is a reverberant environment. Wireless chip-to-chip communication takes place in a confined environment with distance and form-factor limitations. These limitations further aggravate MIMO wireless chip-to-chip communication pushing MIMO communication to use closely spaced transmit and receive antenna elements. Because of form-factor and design limitations, transmit and receive antenna arrays are placed in the near-field of each other. Therefore, the best effort has been made to develop a 2x2 MIMO communication link using SDR based testbed and recreate this environment in a mode-stirred metal enclosure. MIMO channel measurements are conducted in LOS and NLOS multipath fading scenarios in the presence of transmitting and receiving antenna correlations. QPSK digital receiver has been used to understand the near-field link based on BER performance and EVM measurements in a mode-stirred environment. SDR based 2x2 MIMO communication link is tested in metal enclosure in LOS and in NLOS environment when it's empty and when it was loaded with RF absorbers. Two channel BER and EVM results were extracted in LOS and NLOS scenarios both in presence of RF absorbers and in absence of RF absorbers. The experiment for 2x2 MIMO communication link was also repeated in presence of MIMO interference. From the measurements it was shown that the two USRP channel BER and EVM decreases with the increase in Tx interference gain.